Intralesional bleomycin versus cryotherapy for treatment of cutaneous warts: a randomized controlled trial - Rahmatullah, Javaria; Rabia Ghafoor; Muhammad Akhter Anwer (Journal of the Pakistan Medical Association, 2023)
Objective: To evaluate the effectiveness of intralesional bleomycin in comparison to cryotherapy in the treatment of cutaneous warts. Method: The randomized controlled trial was conducted at the Department of Dermatology, Jinnah Postgraduate Medical Centre, Karachi, from January to July 2021, and comprised patients of either gender aged 18-60 years who had cutaneous warts for 1-48 weeks. The subjects were divided into group A treated with 0.1% intralesional bleomycin, and group B were treated with cryotherapy through non probability consecutive sampling. Follow-up examination was done at the 2, 4 and 6 weeks. Data was analysed using SPSS 23. Result: Of the 154 patients, 96(62.3%) were male and 58(37.7%) were females. The overall mean age was 33.253+6.726 years. There were 77(50%) patients in each of the two groups. The therapy after 6 weeks was found to be effective 73(94.8%) group A patients and 57(74%) group B patients (p=0.001). Conclusion: Intralesional bleomycin was found to be more successful than cryotherapy in the treatment of cutaneous warts. Clinical Trial Link: https://clinicaltrials.gov RCT No. (NCT05023408) Key Words: Cryotherapy, Cutaneous, Warts, Intralesional, Bleomycin, Randomised controlled trial.